Peran Pendidikan Agama Islam dalam Menangani Krisis Identitas Generasi Alpha di Era Digital - Siti Latifah Mubasiroh; Nawah Almas Diyau Ma’arif (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Identity crisis is a problem that often occurs when someone is an adult or teenager. Self-identity is a sharpened awareness of one’s self and is used to explain who one is, which includes one’s character and also as a standard of action in evaluating one’s self in the various things one does. The alpha generation, which was born in the digital era with unlimited access to information, is a huge challenge in building this self-identity. This research aims to examine that Islamic Religious Education has a strategic role in developing a person’s self-identity, by providing guidance on spiritual, moral and social values ​​that can help this generation recognize and build a strong self-identity. This research was carried out using the literature study method by examining related references from books and scientific journals.